"I haven't even taken them to the doctors, because I have that fear of what to expect": a qualitative description study exploring perceptions and experiences of early childhood healthcare among ethnically diverse caregivers in Aotearoa New ZealandResearch in context - Nadia A. Charania (Indian); Anjali Bhatia (Indian); Shirleyanne Brown (Ngāpuhi, Ngāti Hau); Tulua Leaumoana (Samoan, Tongan); Hongxia Qi (Han Chinese); Dharshini Sreenivasan (Indian); El-Shadan (Dan); Terryann C. Clark (Ngāpuhi) (Elsevier, 2023)
Summary: Background: Equity underpins Aotearoa New Zealand's publicly funded healthcare system; however, ethnic inequality persists. This qualitative study explored the perceptions and experiences of ethnically diverse parents accessing health services for their children. Methods: A qualitative description methodology informed interviews and focus groups that were conducted with caregivers of preschool aged children who identified as being of Māori, Pacific, Asian and/or European ethnicity (n = 145). Data were analysed following a reflexive thematic analytic approach. Findings: Five themes were constructed. Hierarchies of knowledge and trust Caregivers relied on multiple sources of health information and particularly trusted providers or other caregivers who had children. Relational versus transactional health encounters Caregivers were often disappointed that health providers did not build trusting relationships to support positive experiences. Bad mother vibe Mothers often felt judged by providers when accessing care and felt pressure to conform. The 'slow burn' of waiting Caregivers were often frustrated by how slow and fragmented the health system was, which was particularly distressing if their child was unwell or required referral. Navigating complexity Caregivers had to be proactive and assertive to ensure their child received care amidst the numerous barriers they faced, including discrimination and bias. While many commonalities were shared by ethnicity, unique to Indigenous Māori caregivers were the ongoing colonial traumas that impacted their ability to trust the healthcare system. Interpretation: A non-judgemental, competent, and culturally sensitive approach by healthcare professionals and services may help foster trusting relationships and positive health encounters. Strategies to improve trust, ease of access and navigation are needed to mitigate existing complexity, fragmentation, and counter-intuitive nature of the NZ healthcare system. Caregivers require more autonomy over decisions about their child's care and availability of services that reflect their cultural values. Policies are required to alleviate the indirect costs of accessing healthcare, prioritising of whānau/family-centred care, and addressing pervasive racism and bias within the system. Funding: Health Research Council of New Zealand (19/263) .